Digital Transformation as a Competitive Advantage an empirical study at PT. Bank Negara Indonesia (Persero), Tbk. Region 05 - Mahmudah Kartika Laila; Amie Kusumawardhani (Budapest International Research and Critics University, 2022)
This study aims to find out and analyze the factors of digital transformation in creating competitive advantages, which are carried out empirically at PT. Bank Negara Indonesia (Persero), Tbk Region 05. This research conducts three primary identifications: how companies create digital transformation to be successful, the challenges faced, and the factors of digital transformation that can create a competitive advantage. The data analysis technique used in this study is qualitative research. The digital transformation strategy to be successful is to create digital products that can accommodate the needs of customers, provide convenience in carrying out business activities so that customers are increasingly involved with BNI, able to meet customer expectations or needs, and products that are created by the needs, desires, and abilities of users. The challenges faced include communication networks, especially in remote areas or areas limited by internet signals. Limitations of gadgets that can be supported for mobile banking, limited network coverage at outlets, and limitations of the knowledge of mobile banking users. The digital transformation factors include innovation and application of new ideas or technology to BNI by having a forum for channeling ideas, and creativity, the BNI Business Innovation Award (Binnova). The second factor is the quality of service, PT. BNI continues to improve service quality by providing the best facilities, products, and services that can make it easier for customers to transact. The third factor is the need for organizational learning. BNI personnel intended to be able to measure the soft and hard competencies of each BNI person.